The Effect of Product Quality on Repurchase Intention Mediated by Word of Mouth Variable in Traditional Dayak Cuisine Restaurants in Palangka Raya City - Susanto, Rizky Bagus; Lelo Sintani; Noorjaya Nahan; Luluk Tri Harinie (Dinasti Review, 2025)
This study explore the effect of Product Quality on Repurchase Intention, mediated by Word of Mouth, in traditional Dayak cuisine restaurants in Palangka Raya City. The research aims to analyze how product quality influences customer satisfaction and the likelihood of repeat visits. Employing a quantitative descriptive method, data was collected from customers of Kedai Om Nun and Rumah Makan Samba using a structured questionnaire. The findings reveal that product quality significantly affects repurchase intention, both directly and indirectly through word of mouth. High-quality products lead to positive consumer experiences, fostering word-of-mouth promotion that encourages repeat purchases. These results suggest that maintaining product quality is essential for enhancing customer loyalty and satisfaction in the culinary sector.